2015
DOI: 10.1021/om500829y
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Derivatives of the Natural Polyarsenical Arsenicin A: Biologically Active, Organometallic Arsenic–Sulfur Cages Related to the Minerals Realgar and Uzonite

Abstract: ±)-Arsenicin A (AsA), (±)-1, the first natural polyarsenical to be isolated, has the adamantane-type structure of the mineral arsenolite (As 4 O 6 ), in which three of the oxygen atoms have been replaced by methylene groups to give an organometallic, arsenic− oxygen cage of C 2 symmetry. Heating of a benzene solution of AsA with aqueous sodium sulfide produces, by reductive desulfurization of the intermediate sulfur analog (±)-2, the monosulfide cage (±)-4, which contains two As−As bonds and which has a C 2 -c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 38 publications
(86 reference statements)
0
17
0
Order By: Relevance
“…A comparison between the experimental and calculated 1 H spectra of structure B6 is given in Supplementary Figure S5 . After the extensive testing of several putative structures of the disulfurated arsenicin B, the computational study found agreement for structure B6 , which is the one assigned by experimental data and supported by the X-ray analyzed synthetic compound [ 21 ].…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…A comparison between the experimental and calculated 1 H spectra of structure B6 is given in Supplementary Figure S5 . After the extensive testing of several putative structures of the disulfurated arsenicin B, the computational study found agreement for structure B6 , which is the one assigned by experimental data and supported by the X-ray analyzed synthetic compound [ 21 ].…”
Section: Resultsmentioning
confidence: 75%
“…It is noteworthy that arsenicin B corresponds to one of the four sulfur derivatives obtained when synthetic arsenicin A was treated with an aqueous solution of sodium sulfide in benzene [ 21 ]. The NMR data of the metabolite isolated from E. bargibanti extract are practically superimposable to those reported for the racemic ( R *As, S *As, R *As, R *As)-dihydro-3H-2,6-epithio(1,2,4)triarsolo-(1,2-b)(1,2,3,5) thiatriarsole, which was structurally determined by X-ray diffraction after racemate resolution by chiral column chromatography.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison between the experimental and calculated 1 H spectra of structure B6 is given in Supplementary Figure S5. After the extensive testing of several putative structures of the disulfurated arsenicin B, the computational study found agreement for structure B6, which is the one assigned by experimental data and supported by the X-ray analyzed synthetic compound [21]. Finally, the absolute configuration of arsenicin B was determined by comparing its experimental and time-dependent density functional theory (TD-DFT) calculated electronic circular dichroism (ECD) spectra ( Figure S6).…”
Section: Mar Drugs 2018 16 X For Peer Review 7 Of 14mentioning
confidence: 64%
“…have also been determined, especially in commercial products or biological samples (pharmaceutical formulations, human urine, human or animal blood, human plasma, animal serum, etc.). Another heterogeneous group of analytes, including connectors for building metal-organic frameworks [116,117,124], intermediates for the synthesis of pharmaceuticals [111], natural and synthetic compounds [39,113,121,120], biological compounds [82,112,58,71,78,86,[61][62][63]77,75], natural alkaloids [121], biomolecules [115,54], organometallic compounds [119] and chiral metabolites [103,108,100,97,102,59,63,52] has been enantioseparated with these immobilized polysaccharides CSPs (see Table 2-4). Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%